Selected Aspects of Corporate Social Responsibility of the ICT Sector in Poland − Results of a Study - Teneta, Dorota (Wybrane aspekty społecznej odpowiedzialności przedsiębiorstw sektora ICT w Polsce – wyniki badań, 2025)
Purpose: The main purpose of this article was to identify and evaluate selected aspects of corporate social responsibility (CSR) of ICT companies in Poland, such as CSR-related standards and norms, socially responsible activities in the area of employees, and mechanisms to prevent violations of the law and unethical behaviour. Methodology: the CAWI-type survey was conducted in July-August 2022. The subject of the survey were software houses (Polish and international) operating in Poland. Results: The survey showed that issues such as human capital development, business ethics and compliance, and risk and crisis management are of key importance to the operation of the surveyed companies now and in the future. Conclusions and recommendations: Most of the surveyed entities equated CSR with philanthropic responsibility, and few ICT companies linked CSR with economic responsibility. The analysis of engagement in the employee area showed the high importance given to diversity, equality and inclusion. A limitation of the study was its focus on a few selected aspects of CSR, which did not provide a complete picture of ICT companies’ socially responsible activities. It is worth investigating pro-environmental activities in the future. Originality/value: The rationale for the study was that ICT companies operating in Poland are poorly diagnosed in terms of their CSR. The results of the study may be of value to ICT companies in the context of diagnosing their CSR maturity.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 140-151